Genetic Complexity of the Human Innate Host Defense Molecules, Surfactant Protein A1 (SP-A1) and SP-A2—Impact on Function - Floros, Joanna (2009)
Innate immunity mechanisms play a critical role in the primary response to invading pathogenic microorganisms and other insulting agents. The innate lung immune system includes lung surfactant, a lipoprotein complex that carries out a function essential for life, that is, reduction of the surface tension at the air–liquid interphase of the alveolar space. By means of this function, pulmonary surfactant prevents lung collapse, therefore ensuring normal lung function and lung health. Pulmonary surfactant contains a number of host-defense molecules that are involved in the elimination of pathogens, viruses, particles, allergens, and other insults, as well as in the control of inflammation. This review is concerned with one of the surfactant proteins, the human (h) surfactant protein A (hSP-A), which, in addition to its role in surfactant-related functions, plays an important role in the modulation of lung host defense. The hSP-A locus has been identified with extensive complexity that may have an impact on its function, structure, and regulation. In humans, two genes—SP-A1 (SFTPA1) and SP-A2 (SFTPA2)—encode SP-A, with SP-A2 gene products being more biologically active than SP-A1 in most of the in vitro assays investigated. Although the two hSP-A genes share a high level of sequence similarity, differences in the structure and function between SP-A1 and SP-A2 have been observed in recent studies. In this review, we discuss the human SP-A complexity and how this may affect SP-A function.